2013
DOI: 10.3354/aei00073
|View full text |Cite
|
Sign up to set email alerts
|

Oncorhynchus mykiss escaped from commercial freshwater aquaculture pens in Lake Huron, Canada

Abstract: The fate of farmed fish after escape from aquaculture operations, and their potential ecosystem impacts, remains a primary concern for the sustainable development of this industry. We simulated small-(< 50 fish) and large-scale (500 fish) escape events of rainbow trout Oncorhynchus mykiss from 2 commercial operations in the North Channel of Lake Huron, the site of greatest freshwater production in Canada. Individual fish were either implanted with telemetry transmitters (n = 120) or marked with external tags (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…the exotic rainbow trout (both farm escapees and wild) and the native P. trucha, the former dominating at shallow depths and the latter at greater depths. Escaped (ERT) and wild (WRT) rainbow trout each accounted for c. one third of the total littoral capture (<4 m), coinciding with other studies on depth distribution of farm escapees (Chittenden et al, 2011;Skilbrei, 2012;Patterson and Blanchfield, 2013). Diet differences between species were marked, paralleling the observed segregation by depth.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…the exotic rainbow trout (both farm escapees and wild) and the native P. trucha, the former dominating at shallow depths and the latter at greater depths. Escaped (ERT) and wild (WRT) rainbow trout each accounted for c. one third of the total littoral capture (<4 m), coinciding with other studies on depth distribution of farm escapees (Chittenden et al, 2011;Skilbrei, 2012;Patterson and Blanchfield, 2013). Diet differences between species were marked, paralleling the observed segregation by depth.…”
Section: Discussionsupporting
confidence: 52%
“…These cases highlight the importance of time since escape in the feeding behavior of ERT. In the Canadian lake Huron, normal growth of ERT recaptured next to and distant (500 m) from farms suggested consumption of wild food and/or farm pellets (Patterson and Blanchfield, 2013). In addition, stable isotope analysis showed that ERT captured in tributaries of this lake consumed wild prey, resembling WRT isotopic signals (Johnston and Wilson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations